2007
DOI: 10.1136/gut.2006.091983
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and cardiovascular risk profiles and hepatitis C virus infection in rural Egypt

Abstract: Background and aim: To investigate the relationship between lipid profiles and diabetes with past and chronic hepatitis C virus (HCV) infection among village residents of Egypt. Patients and methods: Fasting lipids and glucose profiles were compared among adults never infected with HCV (negative HCV antibodies), infected in the past (positive HCV antibodies and negative HCV RNA) and chronically infected (positive HCV antibodies and HCV RNA). Results: Of the 765 participants, 456 (59.6%) were female, and median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
70
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 42 publications
(34 reference statements)
15
70
0
1
Order By: Relevance
“…Our findings are consistent with other studies finding low circulating cholesterol and LDL levels in patients with chronic hepatitis C infection (11, 15, 16); our study extends these findings to an American, predominantly genotype 1 cohort, and does so in both a case-control and cohort manner. Our study did not find that pre-treatment lipid levels were predictive of treatment response.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with other studies finding low circulating cholesterol and LDL levels in patients with chronic hepatitis C infection (11, 15, 16); our study extends these findings to an American, predominantly genotype 1 cohort, and does so in both a case-control and cohort manner. Our study did not find that pre-treatment lipid levels were predictive of treatment response.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, high levels of cholesterol, triglycerides, and Ferritin were found in all groups of hepatitis patients whereas significant decreases in hemoglobin and hematocrit were observed in hepatitis patients. The liver is the primary target organ for glucagon action, where it promotes glycogenolysis, gluconeogenesis, and ketogenesis [31]. The availability of serum blood chemistry tests for screening both symptomatic and asymptomatic patients has resulted in a marked increase in the number of abnormal liver chemistry tests that must be interpreted by physicians.…”
Section: Discussionmentioning
confidence: 99%
“…The reported HCV prevalence in Yemen is lower to that in surrounding countries in the region. HCV prevalence increased with age, indicating a accumulative pattern and chronicity (Haidar, 2002;Bajubair et al, 2008;Al Dhahry et al, 2003;Marzouk et al, 2007). The appearance of HCV genotype 1a could probably be due to waves of migration from Asia, Europe or North America (Barth et al, 2006).…”
Section: Discussionmentioning
confidence: 99%